2020
DOI: 10.3390/pathogens9100860
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Different Light Regimes on the Mycoparasitic Activity and 6-Pentyl-α-pyrone Biosynthesis in Two Strains of Trichoderma atroviride

Abstract: The ascomycete Trichoderma atroviride is well known for its mycoparasitic lifestyle. Similar to other organisms, light is an important cue for T. atroviride. However, besides triggering of conidiation, little is known on the physiological responses of T. atroviride to light. In this study, we analyzed how cultivation under different light wavelengths and regimes impacted the behavior of two T. atroviride wild-type strains: IMI206040 and P1. While colony extension of both strains was slightly affected by light,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 70 publications
(91 reference statements)
4
11
0
Order By: Relevance
“…The outcome of mycoparasitic interactions, of course, also depends on additional conditions. For instance, we recently showed that the ability of T. atroviride to mycoparasitise F. oxysporum is light regulated and successful under yellow or red light as well as in complete darkness [ 42 ]. One possible explanation for this phenomenon is that the light-dependent mycotoxin production of F. oxysporum [ 61 ] is so significantly reduced that T. atroviride can overcome its defence response.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The outcome of mycoparasitic interactions, of course, also depends on additional conditions. For instance, we recently showed that the ability of T. atroviride to mycoparasitise F. oxysporum is light regulated and successful under yellow or red light as well as in complete darkness [ 42 ]. One possible explanation for this phenomenon is that the light-dependent mycotoxin production of F. oxysporum [ 61 ] is so significantly reduced that T. atroviride can overcome its defence response.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies showed that deletion of tmk1 and tmk3 significantly reduced the mycoparasitic abilities of T. atroviride in comparison to the wild-type strain [ 32 , 42 ]. By analogy to the role of the F. oxysporum homologue, Fusarium MAPK 1 (Fmk1), in plant sensing [ 77 ], Tmk1 is suspected to be governed by pheromone receptors to sense prey-derived signals.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations